2015
DOI: 10.25011/cim.v38i6.26200
|View full text |Cite
|
Sign up to set email alerts
|

Sex/Gender -Based Pharmacology and Statin Utilization Amongst Elderly Patients with Diabetes

Abstract: Purpose: The purpose of this study was to explore the ten-year trends in utilization of bioequivalent doses of statin amongst elderly patients with diabetes according to sex/ gender in Ontario, Canada. Methods:A cohort of patients with diabetes (>65 years) was constructed using the Ontario Diabetes Database Statin utilization data (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) was obtained from the Ontario Drug Benefit Program for both women and men. Bioequivalent doses for statins were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Multiple studies examining vascular protective agents in Canada have shown an increase in statins and ACEIs/ARBs prescribed and used over the past two decades (10)(11)(12). Estimates from one Canadian province (Ontario) suggest that statin prescriptions in patients with diabetes aged .65 years have increased 53% from 1996 to 2010 and ACEI/ARB prescriptions have increased by 22% over a 6-year period (1995-2001) (11,12).…”
mentioning
confidence: 99%
“…Multiple studies examining vascular protective agents in Canada have shown an increase in statins and ACEIs/ARBs prescribed and used over the past two decades (10)(11)(12). Estimates from one Canadian province (Ontario) suggest that statin prescriptions in patients with diabetes aged .65 years have increased 53% from 1996 to 2010 and ACEI/ARB prescriptions have increased by 22% over a 6-year period (1995-2001) (11,12).…”
mentioning
confidence: 99%